Properties of flocs formed using different coagulants - (:unkn) unknown (I W A PUBLISHING, 2002)
The effects of shear on the formation and break-up of flocs generated using aluminium sulphate (alum), polyaluminium chloride and a cationic polyelectrolyte have been investigated using conventional jar test procedure and by continuous optical monitoring. Using the experimentally determined optimum dosage, the breakage of flocs was followed at a high stirring speed, corresponding to average shear rate (G) of about 330-520 s(-1). Most of the breakage occurred within a few seconds of increasing the shear rate. After each breakage the stirring rate was reduced to the original value to allow the flocs to re-grow. For alum and polyaluminium chloride, it was found that only limited re-growth of flocs occurred indicating a significant irreversibility of the floc break-up process. Residual turbidity increased after floc breakage and re-growth, indicating a reduction in sedimentation rate of the re-grown flocs, consistent with the continuous monitoring results. For the cationic polyelectrolyte, the re-growth of flocs occurred to a much greater extent and floc breakage was almost fully reversible.
Keywords: coagulants; floc breakage; flocculation; floc strength; SIZE